Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China - Chen, Shi-Jing; Peng, Zuo-Gang (Zootaxa, 2019)
A new species of Nemacheilidae, Triplophysa sanduensis sp. nov., is described here based on specimens collected from a small cave in Dengguang Village, Zhonghe Town, Sandu County, Guizhou Province, China. The new species can be distinguished from its congeners by the following combination of characters: branched dorsal-fin rays 8–9; branched pectoral-fin rays 8–9; branched pelvic-fin rays 5; branched anal-fin rays 5; vertebrae 4+37; snout length 45.5–50.1% of head length; postdorsal length 39.0–42.8% of standard length; caudal-peduncle depth/caudal-peduncle length range from 56.4% to 71.9%; the posterior chamber of the gas bladder degenerated; body elongated, covered by scattered scales; eyes present and normal in size, not reduced or absent; and a complete lateral line. A phylogenetic analysis based on the mitochondrial cytochrome oxidase subunit 1 (COI) gene resolved Triplophysa sanduensis as sister to Triplophysa longliensis. Kimura’s 2-parameter genetic distance of the COI gene sequences between these two species was 1.9%.